2017
DOI: 10.1017/s1751731116001518
|View full text |Cite
|
Sign up to set email alerts
|

Influence of high inorganic selenium and manganese diets for fattening pigs on oxidative stability and pork quality parameters

Abstract: Data are scarce regarding combined high Se and Mn supplementation in livestock diets, however, as Se and Mn are functionally related as cofactors of glutathione peroxidase (GPx) and Mn-superoxide dismutase (SOD), respectively, beneficial synergistic effects on oxidative stability of tissues may result. This experiment evaluated the effect of an oversupply of Se and Mn within European legal limits compared with recommendations on performance, oxidative stability of the organism and meat quality in a randomised … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
14
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 27 publications
1
14
0
1
Order By: Relevance
“…Some researches found that Cashmere goat's cashmere and meat are not only affected by animal species, age, sex, feeding methods and other factors, but also closely related to its antioxidant capacity (Qwele et al., 2013; Zervas & Tsiplakou, 2011). Several researchers have shown that dietary supplementation can affect meat color, flavor, and oxidative stability (Rezar et al., 2017; Rossi et al., 2013; Schwarz et al., 2016). Poor feed structure can make organism excessive oxidation and speed up the aging of cashmere goats.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some researches found that Cashmere goat's cashmere and meat are not only affected by animal species, age, sex, feeding methods and other factors, but also closely related to its antioxidant capacity (Qwele et al., 2013; Zervas & Tsiplakou, 2011). Several researchers have shown that dietary supplementation can affect meat color, flavor, and oxidative stability (Rezar et al., 2017; Rossi et al., 2013; Schwarz et al., 2016). Poor feed structure can make organism excessive oxidation and speed up the aging of cashmere goats.…”
Section: Introductionmentioning
confidence: 99%
“…Several researchers have shown that dietary supplementation can affect meat color, flavor, and oxidative stability (Rezar et al, 2017;Rossi et al, 2013;Schwarz et al, 2016). Poor feed structure can make organism excessive oxidation and speed up the aging of cashmere goats.…”
mentioning
confidence: 99%
“…Tous et al [ 10 ] reported that dietary conjugated linoleic acid (CLA) can affect the expression of both porcine lipogenic and regulatory genes including PPARA , PPARG , FASN , SREBF1 , ACACA , LPL , D6D , SCD in a tissue-specific manner. Some studies have described that supplementing the diet with antioxidants or polyphenols can also influence nutrient digestibility, gut microbiota, expression of pro-inflammatory genes and meat quality traits in pigs [ 15 19 ]. Overall, the effects of dietary supplementation on gene expression are mostly unknown.…”
Section: Introductionmentioning
confidence: 99%
“…The Se deficiency in pigs induces sudden death, reduced reproduction and milk production, and impaired immune response ( National Research Council, 2012 ). Positive effects of supplemental dietary Se on meat quality and antioxidative status for pigs have been reported ( Calvo et al, 2017 ; Schwarz et al, 2017 ). However, excessive consumption of Se occurs toxicity in animals.…”
Section: Introductionmentioning
confidence: 99%